A Content and Thematic Analysis of Student International Internship Reports: Basis for Designing Alternative Experiential Learning Activities - Remanente, Maria Cecilia (JPAIR Multidisciplinary Research, 2021)
Schools design internship programs based on intended learning outcomes, which influence their choice of partner training establishments and setting of training activities and duration. An internship is a form of experiential learning, students acquire many unintended discoveries in completing their tasks and interacting with others. This study examines such intended and incidental learning experiences through content and thematic analysis of the internship reports of 26 students of a higher education institution (HEI) located in Cavite, Philippines, who joined either the Thailand Student Internship Abroad Program (SIAP) or the USA Work and Travel Program in 2018 and 2019. These reports contained student reflections, weekly logs of their training activities, and supervisor feedback. The following nodes or units of analysis were used: type of establishment, training area, intentional learning, incidental learning, courses and activities in school that prepared them for their internship, and the supervisors’ comments on the students’ performance. The findings highlight the importance of developing students’ skills in guest handling, food preparation and styling, guiding and escorting, report preparation, and event coordination in preparation for internship. Further, increased cultural knowledge and sensitivity was needed. These findings were used to improve the HEI internship and skills enhancement program for school year 2021-2022, tempered by current situations, most notably the SIAP suspension and limited implementation of onsite local practicum. Alternative experiential learning activities were thus proposed.